A comparing vision of the lakes of the basin of Mexico: from the first physicochemical evaluation of Alexander von Humboldt to the current condition - López-López, Eugenia; Heck, Volker; Sedeño-Díaz, Jacinto Elías; Gröger, Martin; Rodríguez-Romero, Alexis Joseph (Frontiers in Environmental Science, 2023)
The Basin of Mexico is an endorheic lacustrine basin with an outstanding ecological and social history. There is evidence that it hosted human settlers since the late Pleistocene. This basin was home to great antique civilizations and many endemic species of flora and fauna. The main lake in the Basin was the Great Lake of Mexico, which was divided into five lakes and provided goods and services to the native communities. After the Spanish conquest, a rule was established to drain the lakes to prevent flooding in the city. The naturalist Alexander von Humboldt visited Mexico City in the early 1800s, and carried out the first formal scientific water quality analysis of the lakes of the basin. The Basin of Mexico gone through serious modifications due to urbanization and changes of land use reducing the lacustrine area to the virtual extinction of the lakes. The lakes are currently reduced to wetlands accounting for only 2.83 % of the former lake and receiving mainly treated wastewater discharges. We carried out a comparative study between Humboldt’s results and the current characteristics of water from these lake remnants analyzed with the same methods that he used. In addition, we assessed several morphometric parameters and performed water quality assessments using modern methods. Changes in water quality characteristics and ionic composition were detected, with Xochimilco being the lake with the highest water quality score and Texcoco and Chalco showing major alterations. The drastic reduction in the area of the remaining water bodies and the modifications in their water quality are discussed.